Dynamics of particles and fields in gravitational monopole space-times - Seçuk, Muhammed Haluk (My University, 2019)
Bu tez ̧çalışmasında parçacıkların ve alanların davranışını Reissner-Nordström-(A)dS-Monopole uzay-zamanında Klein-Gordon ve Hamilton-Jacobi denklemlerinibelirli durumlar için analitik olarak ̧çözerek inceledik. Buna ek olarak bir karadelikten ışığın sapması ve süperışıma kararsızlığını bu uzay-zaman konfigürasyonuiçin ele aldık ve monopole teriminin etkisini gözlemledik.

In this thesis, we investigate the dynamics of particles and fields in the Reissner-Nordström-(A)dS-Monopole space-time by solving the Klein-Gordon and Hamilton-Jacobi equations. We found an analytical solution to each of these equations incertain conditions. Furthermore, we investigate the light deflection from a blackhole and superradiance on these phenomena in our space-time configuration anddiscuss the effect of the global monopole.
Keywords: Eğri uzay-zamanda klasik alanlar & akışkanlar; Fluids & classical fields in curved spacetime; Genel Görelilik Classical black holes; General relativity; Gravitasyonel Monopoller; Gravitational monopoles; Kara Deliklerleden Işık Sapması; Klasik kara delikler; Light Bending From Black Holes; Superradiance; Süperışıma